Efektifitas P emberian Reward Intrinsik d an Reward Ekstrinsik Terhadap Kepuasan Kerja karyawan Salesmen dimasa Pandemi Covid - 19 - Nurul Nisa; Helmy Adisaksana; Fauziah Fauziah (Fakultas Ekonomi Universitas Islam 45, 2020)
During the COVID-19 pandemic, the Company strives to maintain employee satisfaction during the pandemic. One of the dominant factors that affect employee satisfaction is reward. Rewards are divided into intrinsic rewards and extrinsic rewards. This research was conducted on sales over the counter or OTC in pharmaceutical companies. Sales are usually independent of time and have a high workload. Therefore, companies must know which of the reward systems can increase employee satisfaction. This research is an explanatory qualitative research using SPSS software. The sample in this study were 37 OTC employees. The results of this study are interesting when it is found that extrinsic rewards have a positive and insignificant effect on job satisfaction, then intrinsic rewards have a positive and significant effect on job satisfaction. There is a simultaneous influence between intrinsic and extrinsic rewards on job satisfaction.